answersLogoWhite

0

Assuming that your equation is:_

2X - 8 = -4X +3, adding 8 to both sides gives,

2X = -4X + 3 +8, gives

2X = -4X +11, then adding 4X to both sides,

6X = 11 which gives X = 11/6 = 1.83333.

your original equation was NOT an equation - that is an expression where two things were equal to each other.

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
EzraEzra
Faith is not about having all the answers, but learning to ask the right questions.
Chat with Ezra
BeauBeau
You're doing better than you think!
Chat with Beau

Add your answer:

Earn +20 pts
Q: Can someone Simplify the expression 2x - 8 - -4x plus 3?
Write your answer...
Submit
Still have questions?
magnify glass
imp